Analisis Minat Siswa Sekolah Dasar terhadap Cabang Olahraga Atletik Kids (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Sports play a crucial role in children's holistic development, encompassing physical health, character, discipline, and social skills. Athletics, known as the "mother of all sports," trains essential basic movements like running, jumping, and throwing, which are fundamental for various physical activities. This study aims to analyze the interest of elementary school students in Kids Athletics in SDN 4 Yosomulyo. A quantitative descriptive method was employed , with a total of 75 students from grades IV, V, and VI serving as the sample. The instrument used was a Likert scale questionnaire, which was tested for validity and reliability, yielding a reliability coefficient of 0.839. The research findings indicate that students' interest in Kids Athletics is in the high category. This interest is strongly driven by intrinsic factors, particularly the students' sense of enjoyment and desire to participate. Nevertheless, extrinsic factors such as family support and facility availability also contribute positively. Specific events like Sprint Hurdles and Slalom (Formula 1)  and Sprint Hurdles (Kanga's Escape)  were identified as the most popular among students. The study concludes that elementary school students' interest in Kids Athletics is highly positive, primarily fueled by intrinsic factors, but the roles of school and community in supporting this interest still require optimization.